Evolution of microstructure and mechanical properties of a dissimilar aluminium alloy weldment. (15th January 2016) - Wang, Xiaodong; Mao, Shengcheng; Chen, Peng; Liu, Yinong; Ning, Jin; Li, Haixin; Zang, Ketao; Zhang, Ze; Han, Xiaodong
Abstract: This paper reports a study on the effect of heat input on the microstructure and mechanical properties of dissimilar aluminium alloys joint by MIG welding. The two alloys used are 6N01S-T5 and 7N01P-T4. The 6N01S-T5 alloy exhibited two distinctive sub-zones within its heat affected zone, with the one adjacent to the unaffected parent alloy being the weakest during tensile deformation. The remarkable reduction in the mechanical properties in the weakest region is attributed to the transformation of the precipitates upon welding from smaller sized β″ and β′ precipitates with strong strengthening effect to larger sized β precipitate. The 7N01P-T4 alloy exhibited nucleation of new grains, dissolution of precipitate, and loss of strength in the heat affect zone. Graphical abstract: Highlights: We study the effect of welding heat input on dissimilar aluminium alloys. The microstructures of the two alloys response differently to the heat input. The 6N01 alloy exhibited two distinctive HAZs, while 7N01 alloys exhibited one. The mechanical strength of the 6N01 alloy was more reduced than of the 7N01 alloy.